The Adoption of Electric Vehicles in the Sultanate of Oman: A Conceptual Study - Said Alsalmi H.A.; Thiruchelvam S. (World Scientific and Engineering Academy and Society, 2024)
This research aims to propose a conceptual framework that links Personal and Technological Factors with Electric Vehicle (EV) adoption in Oman, and to test the validity and reliability of the research model. Based on the Social Cognitive Theory, the framework contained Omani Social Norms, Perceived Usefulness (as Personal Factors), the Governments Personnel Information Technology IT Competencies, Electric Vehicles System Quality, and the Lack of charging infrastructure (as Technological Factors) as independent variables